2020
DOI: 10.1242/dmm.043513
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Nurr1 is up-regulated in amyotrophic lateral sclerosis patients and SOD1-G93A mice

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that affects both lower and upper motor neurons (MNs) in the central nervous system (CNS). ALS etiology is highly multifactorial and multifarious, and an effective treatment is still lacking. Neuroinflammation is a hallmark of ALS and could be targeted to develop new therapeutic approaches. Interestingly, the transcription factor Nurr1 has been demonstrated to play an important role in inflammatory process in several neurological disorders, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
0
7
0
1
Order By: Relevance
“…Despite Nurr1 was mainly expressed on neurons, bodies of literature had recently reported the antineuroinflammatory effects of Nurr1 in various disease models [34,40,46]. Meanwhile, taken into account that neuroinflammation was an important pathophysiological process involved in the early brain injury of SAH so that we could not ignore this point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite Nurr1 was mainly expressed on neurons, bodies of literature had recently reported the antineuroinflammatory effects of Nurr1 in various disease models [34,40,46]. Meanwhile, taken into account that neuroinflammation was an important pathophysiological process involved in the early brain injury of SAH so that we could not ignore this point.…”
Section: Discussionmentioning
confidence: 99%
“…A similar phenomenon was observed in the HT22 cells; moreover, the effect of AQ on the expression of nuclear Nurr1 was in a dose-dependent manner (Figure 6(c)). Numerous studies had reported that Nurr1 exerted an anti-inflammatory effect by regulating NF-κB in vitro and in vivo [38][39][40]. The stimulation of Nurr1 with AQ could decrease the expression of nuclear NF-κB in the rat models and HT22 cells (Figures 6(a) and 6(c)).…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 92%
“…The nuclear receptor Nurr1 (NR4A2) plays critical roles in both developing and adult midbrain dopaminergic neurons, controlling the transcription of genes required for the synthesis ( TH ) and vesicular packaging ( VMAT2 ) of dopamine, among other essential biological functions (e.g., management of oxidative stress, responsiveness to inflammatory signals). Clinical and animal data indicate that disrupted Nurr1 function contributes to inducing the dysregulation of dopaminergic neurons observed in the early stages of Parkinson’s disease (PD), as well as other dopamine-related CNS disorders (e.g., ALS, MS). , Unraveling the complex biology of Nurr1 would be facilitated by bona fide Nurr1-targeting synthetic small molecules that can be used to directly modulate the receptor. Phenotypic assays have identified synthetic ligands that reportedly up-regulate transcription and protein levels of Nurr1 target genes, provide some degree of neuroprotection, and improve behavioral deficits in mouse models. However, there is little evidence that these compounds directly activate endogenous Nurr1, with the exception of the antimalarial drug amodiaquine and related analogs. , …”
mentioning
confidence: 99%
“…These include kinesins (e.g., KIF5C and KIFC3) and the dynactin subunit DCTN1 which are involved in axonal transport [ 107 , 108 , 109 ], neurotrophic factors (e.g., Trk-B, BDNF, PI3K, AKT, NFκB, GSK3β, and FASL) involved in cell proliferation and differentiation [ 110 ], apoptotic regulatory proteins CyFIP2 and RbBP9 [ 111 ], the vascular endothelial growth factor-A (VEGF-A) and chemokine ligand (CCL2) which are thought to play a role in neuroprotection [ 112 ], and the transcription factor Nurr1 which is involved in neuroinflammation [ 113 ]. However, most of these mRNAs are similarly dysregulated in other neurodegenerative diseases or have not been tested for ALS specificity, with exceptions for FasL mRNA, which showed a significant increase in the peripheral blood leukocytes (PBL) of ALS patients relative to PD, ataxia, and healthy controls [ 114 ], and Nurr1, which was downregulated in the peripheral blood of PD patients [ 114 ] and upregulated in ALS [ 113 ]. Further, VEGF-A and CCL2 mRNAs showed higher elevation in the PBL of Indian ALS patients with respiratory dysfunction and could therefore be disease progression biomarkers [ 112 ].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%